Investigasi Kekakuan Pada Pelat Baja Lunak Dengan Pembentukan Metode Dimple Dies Triangle Profile - Risky Arisandi; Erwanto Erwanto; Harwadi Harwadi (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
This study aims to analyze the effect of variations in the number and diameter of dimple holes on the stiffness of mild steel plates using the Dimple Dies Triangle Profile forming method. Plate stiffness is important for reducing vibrations, especially in vehicle components. The material used was a 0.6 mm thick galvanneal plate, with dimple diameters of 25 mm and 30 mm, and hole quantities of 16 and 20. Testing was conducted using a Vibroport 80 device to measure natural frequency as an indicator of stiffness. The experimental design employed the Taguchi method with an L4 orthogonal array to analyze the influence of each parameter. The results showed that the number of dimple holes significantly affected the plate’s natural frequency, while the dimple diameter had no significant effect. The optimal combination producing the highest stiffness was a 25 mm dimple diameter with 16 holes. ANOVA and S/N ratio analysis supported these findings, indicating that the number of holes contributed more than 90% to the variation. This research is expected to serve as a reference for developing stiffer and more vibration-resistant metal plate designs, particularly for automotive and other engineering structure applications.